Role of Regulated Proteolysis in the Communication of Bacteria With the Environment - Wettstadt, Sarah; Llamas, María A. (Frontiers in Molecular Biosciences, 2020)
For bacteria to flourish in different niches, they need to sense signals from the environment and translate these into appropriate responses. Most bacterial signal transduction systems involve proteins that trigger the required response through the modification of gene transcription. These proteins are often produced in an inactive state that prevents their interaction with the RNA polymerase and/or the DNA in the absence of the inducing signal. Among other mechanisms, regulated proteolysis is becoming increasingly recognized as a key process in the modulation of the activity of these signal response proteins. Regulated proteolysis can either produce complete degradation or specific cleavage of the target protein, thus modifying its function. Because proteolysis is a fast process, the modulation of signaling proteins activity by this process allows for an immediate response to a given signal, which facilitates adaptation to the surrounding environment and bacterial survival. Moreover, regulated proteolysis is a fundamental process for the transmission of extracellular signals to the cytosol through the bacterial membranes. By a proteolytic mechanism known as regulated intramembrane proteolysis (RIP) transmembrane proteins are cleaved within the plane of the membrane to liberate a cytosolic domain or protein able to modify gene transcription. This allows the transmission of a signal present on one side of a membrane to the other side where the response is elicited. In this work, we review the role of regulated proteolysis in the bacterial communication with the environment through the modulation of the main bacterial signal transduction systems, namely one- and two-component systems, and alternative σ factors.